The Influence of Professionalism and Achievement Motivation on the Performance of Junior High School Teachers in Binjai City - Wahyuni Kesuma; Mesiono; Sakholid Nasution; Selamat Pasaribu (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to find out: the influence of professionalism on teacher performance; the influence of professionalism on achievement motivation; the influence of achievement motivation on teacher performance; and The simultaneous influence of professionalism and achievement motivation on teacher performance. This study uses a quantitative method with the subject of the study being kindergarten teachers in Binjai City with a population of 549 and a sample of 231 people. Sampling was carried out with total sampling. The research method is a path analysis that aims to test theories and obtain research information. The results of this study are presented: 1) there is a direct influence between professionalism and teacher performance with a correlation coefficient of rX2X4 = 0.075. The effective contribution given by the professionalism variable to teacher performance is 7.5%. 2) there is a direct influence between professionalism and achievement motivation with a correlation coefficient rX2X3 = 0.811. The effective contribution given by the professionalism variable to achievement motivation was 8.1%. 3) there was a direct effect between achievement motivation and teacher performance with a correlation coefficient of rX3X4 = 0.001. The effective contribution given by the achievement motivation variable to teacher performance is 1%. 4) there was a simultaneous influence between organizational climate, professionalism, and achievement motivation on teacher performance with a correlation coefficient of rX1X2X3X4 = 0.092. The effective contribution given by the variables of organizational climate, professionalism and achievement motivation to teacher performance was 9.2%.